Experimental Evaluation of Piezoelectric Vehicle Speed Sensor for Smart Highways: A Progress Report - Underwood, Ivan; Bailen, Kara Leah; Dellapenna, Francis J; Taha, Luay Yassin; Abdeltawab, Hussein M; Anwar, Sohail (International Conference on Renewable Energy Research and Applications (Online), 2023)
In smart highways and smart roads, detection and measuring the vehicle speed is essential for monitoring purposes and proper traffic and lane keeping operations. In our previous work, we presented a piezoelectric harvester and speed sensor by embedding, in the asphalt, two piezoelectric modules at a known distance. Each one generates pulses when stressed by the vehicle wheels. These pulses are collected by the Arduino microcontroller. Then, the vehicle speed is estimated using an estimation algorithm. The practical testing was carried out using the Hamburg Wheel Tracking machine which has limitation in varying the speed. In this work, we extend the practical testing of the system using two free fall objects that sequentially stress the two piezoelectric modules, thus generating two pulses have a time delay that is controlled using timing circuit. The pulses are acquired using the Arduino microcontroller. Then, the vehicle speed is estimated from the time difference between the two pulses. The experiment is repeated for different time delays to evaluate the sensing accuracy. Results have shown considerable accuracy in sensing the speed when the time delay between the pulses varies from 2s to 10s.